KERAGAAN KUALITATIF KLON KENTANG (G0) DARI STEK MINI DALAM RUMAH KETAT SERANGGA - Gunarto, Anton (Jurnal Matematika Sains dan Teknologi, 2008)
The purpose of the research is to investigate the phenotypic performances as qualitative assessment characters of three potato clones resulted from protoplasm fusion (A5) and two clones from botany seeds (PAS3063 and PAS3064) which had been identified to be resistant from bacterial wilt disease (Ralstonia solanacearum). The commercial potato varieties (Granola and Atlantic) were used as a comparison varieties. All five varieties were produced from mini graft. The result of qualitative performance that more prominent were on A5 clone with the characters that the branch was red, tuber skin was purple/violet and its ability produce flowers. Meanwhile, the branch of another clone was green, tuber skin was yellow/brown, and it does not produce much flowers. The color of tuber flesh were white except on Granola which was yellow. The result of cluster analysis that based on the morphologic character from each plant showed that PAS3063 was closed to Atlantic variety characteristic, PAS3064 was closed to Granola variety, and A5 different from both commercial varieties.There fore, it is proposed that PAS3063 and PAS3064 can be used as substitutes for commercial cultivars, while further consideration should be made for A5 since it is signifoutly different with the familiar cultivars.